Optimising extraction of microalgal oil using accelerated solvent extraction by response surface methodology - Ahmad, Farah; Zhang, Zhanying; Doherty, William O. S.; O'Hara, Ian M. (Taylor's University, 2018)
The extraction of oil from biomass is one of the most important aspects in the harvesting of microalgae for the production of oil. Efficient extraction technique is important for the quantification of oil content in biomass. Solvent extraction is typically employed for the extraction of oil. Accelerated Solvent Extraction (ASE) is an automated pressurised liquid extraction technique that provides rapid and effective extraction process. There are limited studies on the effects of extraction conditions using the ASE technique to achieve optimum oil yield. The aim of this study was to optimise the extraction of oil using the ASE technique by response surface methodology. A face-centred central composite design (CCD) was used to evaluate the effects of static cycle (1 to 6 cycles), static time (2 to 10 min) and temperature (100 to 160 °C) on oil extraction. The optimum condition was found to be at 4 static cycles, static time of 6 min and temperature of 160 °C, with an oil yield of 34.9%. From the ANOVA results, R2 of the mathematical model is 0.9970. This study showed an improvement in the oil yield using the optimum condition for ASE, where the optimum condition resulted in 1.34 fold increases in oil yield from the control run.